Fruit tree leaves as valuable new source of tocopherol and tocotrienol compounds. (30th August 2021) - Wojdyło, Aneta; Turkiewicz, Igor Piotr; Tkacz, Karolina; Hernandez, Francisca
Abstract: BACKGROUND: Nowadays it is highly important to find new, cheap and widely available sources of tocopherol and tocotrienol compounds, and leaves are promising unconventional sources. The main goal of this study was to extend the currently limited knowledge concerning tocopherol and tocotrienol isomers composition determined using ultra‐high performance liquid chromatography with fluorescence detection analysis for various fruit tree leaves such as apple, pear, quince, apricot, peach, plum, sour cherry and sweet cherry. The leaves were collected 2 weeks after tree blooming and after fruit collection. Tocopherol and tocotrienol isomers were identified and quantified for the first time in all fruit tree leaves. RESULTS: The total tocopherol content ranged from 203.34 to 260.86 μg g −1 dry weight for spring leaves and from 23.83 to 235.62 μg g −1 dry weight for autumn leaves and consisted mainly of α‐tocopherol. The rest of the isomers of tocopherol and tocotrienols were also found, but in trace amounts. A significantly lower content of tocopherols and tocotrienols was detected in leaves after autumn collection of fruits compared to leaves collected after blooming. Among the analyzed leaves, time collected and species were significantly more important than their cultivars. Regarding quantification analysis, apricot > peach > > plums > apples leaves were identified as the best sources of tocopherols, and sweet and sour cherry leaves exhibited a lower content. CONCLUSION: Fruit tree leaves are a novel significant source and good material for isolation of α‐tocopherol for application in cosmetics, pharmaceuticals or in the food industry – for example, production of beverages or other functional foods. © 2021 Society of Chemical Industry.